Varicocele - literature review - Wojciech Sowiński; Wiktoria Walentyn; Maria Wachowska; Marek Molenda; Oliwia Woszczyńska; Paweł Rycąbel; Mateusz Romaniuk; Mateusz Paniak; Marta Szymura; Agnieszka Wojciechowska; Michał Krawczyk; Michał Zdybel (Quality in Sport)
Introduction and objective